CHANGE OF HEARING FUNCTION AT RENAL FAILURE - Александрук, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
We examined 40 patients of age 20 to 70 years old with chronic renal failure of different severity. 20 examined patients had impaired hearing function. Neuronsensoric portion of hard hearing was determined during examinations. At the beginning of chronic renal failure lost of hearing was observed in 45% cases, at progression of intoxication syndrome in 77,7% cases.